Trust - Akhmetova, Elmira (2016)
1. What is the meaning of trust? 2. Its position in Islam. 3. Why it is important? And what is its implication to us, the teaching and administrative staff of the biggest kulliyah of the largest and one of the most important Islamic universities of the Muslim world?